Edo Culture : daily life and diversions in urban Japan, 1600-1868 - Nishiyama, Matsunosuke, 1912-2012 (University of Hawaiì Press, 1997)
"Nishiyama Matsunosuke is one of the most important historians of Tokugawa (Edo) popular culture, yet until now his work has never been translated into a Western language. Edo Culture presents a selection of Nishiyama's writings that serves not only to provide an excellent introduction to Tokugawa cultural history but also to fill many gaps in our knowledge of the daily life and diversions of the urban populace of the time. Many essays focus on the most important theme of Nishiyama's work: the seventeenth to nineteenth centuries as a time of appropriation and development of Japan's culture by its urban commoners."--Jacket